MULTICULTURAL DYNAMICS IN THE ELECTION OF A NON-MUSLIM VILLAGE HEAD IN A MUSLIM-MAJORITY COMMUNITY: A CASE STUDY IN PERGUROAN VILLAGE, BANGUN PURBA SUBDISTRICT, DELI SERDANG REGENCY - Dede Khairani; Ahmad Darlis; Akmal Shah; Muhammad Syawal Karo-karo (Pena Cendekia Insani, 2025)
This study aims to examine the multicultural dynamics that emerge in the election process of a non-Muslim village head within a Muslim-majority community, using a case study of Perguroan Village, Bangun Purba Subdistrict, Deli Serdang Regency. The main focus of this research is to explore how social interactions, tolerance, and local democratic practices are carried out in a context of religious diversity that holds the potential for tension. The research employs a qualitative approach, with data collected through in-depth interviews, participant observation, and document analysis. The findings reveal that, despite the potential for resistance based on religious identity, the community of Perguroan Village exhibits a high level of acceptance toward a non-Muslim village head. This is made possible by the strong presence of local values such as gotong royong (mutual cooperation), respect for differences, and a long-standing history of interfaith coexistence. This study affirms that multicultural practices at the local level can function harmoniously when supported by an inclusive culture and leadership that is capable of bridging differences.